Implikasi Pendidikan Islam Dalam Pendidikan Anak Menurut Irwan Prayitno - Zuyyina Candra Kirana (Nazhruna: Jurnal Pendidikan Islam, 2018)
Education for children is a principle of human happiness must begin from childhood and is the best time to learn the correct method of life. Ability to capture and follow (lessons), and the sensitivity of receiving knowledge is still very strong in children. According to. Irwan Prayitno child is a very special figure, which in its development requires guidance and guidance from parents in order to realize the figure of a virtuous child. Educating children requires detailed description and precise data collection of the child's behavior. Data collection is needed to direct the potential in children. According to Irwan Prayitno in realizing the figure of a virtuous child, the child requires proper upbringing. According to him the proper education is education based on Islamic values. Because Islam is a perfect religion. It covers all aspects of human life. Including the issue of children's education who get a place in it, Islam is very concerned about families and children who are the basic foundation. on Islamic values as a reference in formulating the applied education. Based on the analysis, there are many similarities between educational concepts. Irwan Prayitno with the concept of Islamic education. So indirectly education. Irwan Prayitno has a close relationship with Islamic education.